PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP KINERJA KEUANGAN - Nuryanti, Novita Ayu; Suryandani, Wulan (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023, 2025)
Financial performance is an achevment achieved by the management of an organization in the efficient management and use of its assets over a certain period of time. This research aims to clarify the connection between the financial performance of food and beverage firms listed on the indonesia Stock Exchange from 2019 to 2023 and liquidity, company size, and leverage. This study, financial performance was measures by the return on assets, liquidity is measured by the current ratio, company size is measured by size and leverage is measured by the debt to equity ratio. The population considered includes all food and beverage firms registered on the IDX between 2019 and 2023. This study uses the documentation method as a data collection technique, while for sample selectin with purposive sampling technique. There are 55 observations and 11 companies in the study sample. The technique used for data analysis is multiple linear regression analysis. IBM SPSS 25 is used for data processing. The results showed that liquidity has no effect on financial performance, company size has a positive effect on financial performance meanwhile leverage has a negative effect on financial performance.